Effectiveness of musical toothbrush on oral debris and gingival bleeding among 6-10-year-old children: A randomized controlled trial - Nivedha Subburaman; Parangimalai Diwakar Madan Kumar; Kiran Iyer (Wolters Kluwer Medknow Publications, 2019)
Context: Motivation serves to be an integral part of health promotion to children at the learning phase of their life. Aim: Evaluation of the effectiveness of musical toothbrush over regular toothbrush in the debris and gingival bleeding scores among children. Settings and Design: This was a single-blinded parallel, randomized controlled trial conducted among 6-10-year-old schoolchildren in Chennai. Methods: One hundred participants with allocation ratio of 1:1 were assigned to musical and regular toothbrush group by simple randomization. After baseline evaluation (T0) of Debris Index-Simplified (DI-S) and Gingival Bleeding Index (GBI), outcome variables were assessed for a period of 3 months (T1, T2, and T3). Statistical Analysis Used: Friedman test and Mann-Whitney statistical test were used to compare the outcome variables within and across the two groups. Results: Thirty-two boys and 68 girls (mean age: 8.53 years) participated in the study. Statistically significant difference was seen in DI-S score among musical toothbrush group (mean: 0.50 [T3] and GBI score: 8.18% [T3]) when compared to regular toothbrush group (mean: 1.59 [T3] and GBI score: 23.54 [T3]) at the end of the 3rd month. Conclusion: Although both the musical and regular toothbrushes effectively reduced the DI-S and GBI scores, former showed effective change among children when compared to the latter.